Efficient adsorption of 4-Chloroguiacol from aqueous solution using optimal activated carbon:Equilibrium isotherms and kinetics modeling - Rahim, Afidah Abdul; Garba, Zaharaddeen N. (Elsevier, 2016)
The optimal activated carbon produced from Prosopis africana seed hulls (PASH-AC) was obtained using the impregnation ratio of 3.19, activation temperature of 780 C and activation time of 63 min with surface area of 1095.56 m2/g and monolayer adsorption capacity of 498.67 mg/g. The adsorption data were also modeled using five various forms of the linearized Langmuir equations as well as Freundlich and Temkin adsorption isotherms. In comparing the legitimacy of each isotherm model, chi square (v2) was incorporated with the correlation coefficient (R2) to justify the basis for selecting the best adsorption model. Langmuir-2 > Freundlich > Temkin isotherms was the best order that described the equilibrium adsorption data. The results revealed pseudo-second-order to be the most ideal model in describing the kinetics data.